Knowledge Of Children Aged 5-6 Years About the Cultural Values of the Traditional Congklak Game - Putri, Shaffira Meirizka; Amirul Mukminin, Amirul Mukminin, S. Pd., M.Kes (Universitas Negeri Semarang, 2025)
The aim of this researcher is to determine the knowledge of children aged 5-6 years about the cultural values of the traditional game congklak. This research uses a quantitative approach, namely a type of experimental research with a one group pretest posttest design. The research population was 30 Nida Asyifa Islamic Kindergarten students. The sampling technique uses a proportionate stratified random sampling technique, which means a proportion-taking technique to obtain a representative sample, taking subjects from each or every region determined to be balanced or proportional to the number of subjects. Data collection techniques use questionnaires and documentation. The data analysis technique uses inferential statistics with hypothesis testing using paired sample T-Test, N-Gain score. The results of the research from the t-test calculations obtained a value of t count > t table, namely 9,381 > 1,699 with a significance value of 000<0.05 so that Ho was rejected and Ha was accepted, meaning that there was an increase in the cultural values of children aged 5-6 years from the traditional game congklak significantly 89.9%. There is an average difference in the level of children's cultural values before and after being given treatment. The results of the data normality tst show that the Asymp sig (2-tailed) significance value of 0.107 is greater than 0.05 it can be concluded that the distribution is normal. And the results of the n-gain test are in the criteria of moderate improvement with a percentage of 0.3≤ g ≤ 0.7 because you get a result of 0.32 or at a percentage of 32%. From the results of data analysis it can be concluded that the increase in knowledge of children aged 5-6 years about cultural values in the medium category in the traditional game congklak. This shows that the traditional game congklak is effective in increasing cultural values. Suggestions put forward in this research: (1) it is hoped that traditional games will be facilitated at the Nida Asyifa Islamic Kindergarten school and provide facilitators to introduce children to the congklak game so that there is a sense of interest in trying it and a feeling of love. (2) can stimulate all aspects of children's development through the traditional congklak game.